Activation and Desensitization of Hippocampal Kainate Receptors - Wilding, Timothy J. (J Neurosci, 1997)
We have used whole-cell recordings and rapid agonist applications to characterize the physiological properties of kainate receptors expressed by rat hippocampal neurons in dissociated cell culture. Activation of NMDA and AMPA receptors was prevented by inclusion of the noncompetitive antagonists MK-801 (2 μm) and GYKI 53655 (100 μm), respectively. In the presence of these inhibitors, both kainate (EC(50) = 23 μm) and glutamate (EC(50) = 310 μm) evoked desensitizing currents. Maximal peak currents for kainate with GYKI 53655 were 15 ± 3% as large as in control solutions without GYKI. In contrast to currents mediated by AMPA receptors, kainate currents recorded in GYKI were blocked potently by lanthanum (IC(50) = 2 μm) and were desensitized by 1 μm 2S,4R-4-methylglutamate (SYM 2081). Coapplication of either 5 μm AMPA or 500 μm aspartate had little effect on responses to kainate, although AMPA alone elicited current at 1 mm. In most cells, the currents evoked by kainate, glutamate, and SYM 2081 varied linearly with membrane potential and reversed near 0 mV. Kainate elicited substantial current at steady state (∼30% of peak), whereas responses to glutamate and SYM 2081 desensitized almost completely within 0.2–2 sec. Inhibition produced by a 10 sec desensitizing prepulse was half-maximal at 0.22 μm for SYM 2081 and 13 μm for glutamate. Recovery from desensitization to kainate and glutamate was >80% complete within 60 sec but was three- to fourfold slower after exposure to SYM 2081. Exposure to Concanavalin A blocked desensitization of the currents but also reduced the peak current amplitudes. Collectively, these results confirm that kainate-preferring receptors underlie the currents evoked by kainate, glutamate, or SYM-2081 in the presence of GYKI 53655; they are not mediated by electrogenic transport or by AMPA-preferring receptors that are insensitive to GYKI. In contrast to previous work on embryonic hippocampal neurons, our results show that the properties of kainate receptors expressed by cells from older animals are distinct from those displayed by homomeric assemblies of the GluR6 subunit.